Recentivity and inerciality of philosophy - Sztumski, Wiesław (Folia Philosophica, 2000)
Recentivity understood as a capacity to be here and now is an attribute of philosophy: a doctrine, conception, or idea of whatever kind may become actualised in the future (i.e. in another „here and now”) in specific social conditions. And the more open a given doctrine is, the more recentivisty it becomes. Inertiality is also an attribute of philosophy, and it manifests itself in the capacity to retain certain philosophical doctrines and ideas in the memory of subsequent generations. Philosophy is a discipline with the highest degree of inertivity, and therefore it is the most historical. As opposed to the sciences, it cannot be practised without referring to history, i.e. without a possibility of repetitions. Both attributes - recentivity and inertiality - belong to the essence of philosophy and of its functioning.